Fundamentals of electro-optic systems design communications, lidar, and imaging - Karp, Sherman (Cambridge University Press, 2013)
Using fundamentals of communication theory, thermodynamics, information theory and propagation theory, this book explains the universal principles underlying a diverse range of electro-optical systems. From fiber optics and infra-red imaging to free space communications and laser remote sensing, the authors relate key concepts in science and device engineering to practical systems issues. A broad spectrum of coherent and incoherent imaging and communications systems is considered, accompanied by many real-world examples. The authors also present new insights into LIDAR and free space communications and imaging, providing practical guidance on identifying the fundamental limitations of transmission and imaging through deleterious channels. Accompanied by online examples of processed images and videos, this uniquely tailored guide to the fundamental principles underlying modern electro-optical systems is an essential reference for all practising engineers and academic researchers in optical engineering